STIMULUS OF FITRAH IN HANDLING DISORIENTATION - Ahmad Misbahul Anam (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
Disorientation necessitates natural stimuli as the answer to human psychological aspects. This effort is carried out through spiritual values ​​as a means of the soul for damage to orientation which really needs to be returned to its original position as created by Allah SWT. Research observes social phenomena that are minus the norm as many have reported through the mass media. The problem data is tried to be confirmed through the revelation approach as information which provides many answers to psychiatric problems, accompanied by explanations from experts involved in handling moral problems. This finding is intended as a scientific contribution related to the handling of these psychological problems.